Catalytic layer with layered ionomer distribution and preparation method and application thereof

Through the double-spray alternating ultrasonic spraying method, long side chain ionomers and short side chain ionomers are sprayed layer by layer to form a multi-layer composite catalytic layer, which solves the problem of low oxygen transmission efficiency in the existing fuel cell catalytic layer and significantly improves the oxygen mass transfer efficiency and electrochemical performance.

CN119725587AActive Publication Date: 2025-03-28SHANGHAI JIAOTONG UNIV +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411931974.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The oxygen transmission efficiency in the catalytic layer of existing fuel cells is low, and the distribution of the catalyst surface and ionomers cannot be accurately controlled, resulting in large oxygen mass transfer resistance, affecting battery performance.

Method used

The double-spray alternating ultrasonic spraying method is used to spray the long side chain ionomer solution and the short side chain ionomer catalyst-containing slurry layer by layer to form a multi-layer composite catalytic layer to accurately control the ionomer distribution and reduce the oxygen mass transfer resistance.

Benefits of technology

It significantly improves the oxygen mass transfer efficiency and electrochemical performance, reduces the local oxygen mass transfer resistance, improves the catalyst utilization rate, and builds an efficient proton conduction network.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725587A_ABST
    Figure CN119725587A_ABST
Patent Text Reader

Abstract

The invention relates to a catalyst layer with layered ionomer distribution and a preparation method and application thereof. The catalyst layer is of a multi-layer composite structure and comprises an ionomer solution layer and a catalyst slurry layer which are alternately sprayed on the substrate layer by layer; an ionomer in the ionomer solution layer is a long side chain ionomer; the slurry of the catalyst slurry layer comprises a short side chain ionomer and a Pt / C catalyst, and the mass ratio of the short side chain ionomer to the carbon carrier is 0.05-0.2. The preparation method comprises the following steps: respectively preparing an ionomer solution and catalyst slurry; two independent controllable ultrasonic nozzles are arranged, the two ultrasonic nozzles are alternately used for spraying an ionomer solution layer and a catalyst slurry layer on a heated substrate, and finally the catalyst layer is obtained. Compared with the prior art, accurate layering and control of the catalyst and the ionomer are realized through a double-nozzle alternate spraying technology, the internal structure of the catalyst layer is optimized, and the electrochemical performance of the fuel cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a catalyst layer with layered ionomer distribution, a preparation method and an application thereof. Background Art

[0002] As an efficient and environmentally friendly clean energy technology, proton exchange membrane fuel cells (PEMFCs) have broad application prospects, especially in the fields of transportation, fixed power supplies and portable devices. However, the commercialization process of PEMFCs is still limited by many challenges. Among them, the low oxygen transfer efficiency in the catalyst layer is one of the key issues affecting battery performance. This problem is particularly evident in low-platinum fuel cells. This is mainly due to the excessive degree of ionomer coating on the catalyst surface in the catalyst layer. Under high current density, due to the traditional catalyst layer preparation method of mixing the catalyst and the ionomer and spraying them together, an overly thick ionomer coating layer is formed on the catalyst surface, which seriously hinders the transmission of oxygen to the catalytic active sites, increases the local oxygen mass transfer resistance, and limits the oxygen reduction reaction.

[0003] Existing improvement measures are mainly focused on optimizing the catalyst layer slurry formula. For example, the resistance to oxygen transmission can be reduced by reducing the ionomer content in the catalyst slurry, adjusting the I / C ratio, or changing the type of ionomer. However, these methods often affect the construction of the proton conduction network in the catalyst layer due to the reduction of the ionomer content, and cannot accurately control the distribution of ionomers on the catalyst surface. Especially when a higher total ionomer content is required to ensure proton conduction, an excessively thick ionomer coating layer will still significantly affect the transmission of oxygen to the catalyst surface, thereby reducing the overall performance of the cell. Therefore, it is of great practical significance to develop a catalyst layer preparation method that can accurately control the distribution of ionomers on the catalyst surface and the directional distribution of ionomers in the catalyst layer, and it has gradually become one of the core issues that need to be solved in the PEMFC field.

[0004] In addition, in the existing preparation method of the catalytic layer, the catalyst and the ionomer are usually mixed and sprayed together, and the distribution of the ionomer on the catalyst surface cannot be effectively controlled. This mixed spraying method causes an excessively thick ionomer coating to form on the catalyst surface, significantly increasing the local oxygen mass transfer resistance and affecting the efficiency of the oxygen reduction reaction. Secondly, due to the inability to accurately control the distribution of the ionomer, the ionomer layer on some catalyst surfaces is too thick and some is too thin, resulting in a low catalyst utilization rate. Especially when a higher overall ionomer content is required, many active sites are covered by an excessively thick ionomer layer, accompanied by a significantly increased local oxygen mass transfer resistance. In addition, the traditional mixed spraying method also has major deficiencies in forming a proton conduction network, and often requires a higher local ionomer content to ensure proton conduction, which further exacerbates the oxygen transfer resistance.

[0005] Therefore, in view of the problems existing in the above-mentioned proton exchange membrane fuel cell catalyst layer, it is urgent to develop a new type of fuel cell catalyst layer. Summary of the invention

[0006] The purpose of the present invention is to overcome the defects of the prior art in low oxygen transmission efficiency and inability to control the distribution of catalysts and ionomers, and to provide a catalytic layer with layered ionomer distribution and its preparation method and application.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] The present invention provides a catalytic layer with layered ionomer distribution, wherein the catalytic layer is a multi-layer composite structure, which includes an ionomer solution layer and a catalyst slurry layer formed by alternately spraying layer by layer on a substrate;

[0009] The ionomer in the ionomer solution layer is a long side chain ionomer;

[0010] The slurry of the catalyst slurry layer includes short side chain ionomer and Pt / C catalyst, wherein the mass ratio of the short side chain ionomer to the carbon carrier is 0.05-0.2.

[0011] Furthermore, the catalytic layer has a total of N layers, where N is an odd number; wherein the 1st, 3rd, 5th ... Nth layers are ionomer solution layers, and the 2nd, 4th, 6th ... (N-1)th layers are catalyst slurry layers.

[0012] Furthermore, the long side chain ionomer is selected from Nafion series ionomers.

[0013] Furthermore, the short side chain ionomer is selected from Aquivion series ionomers.

[0014] Furthermore, the total mass ratio of the ionomer to the carbon carrier in the catalytic layer is 0.75-0.85, preferably 0.8.

[0015] Furthermore, the platinum loading of the catalytic layer is 0.15-0.25 mg / cm 2 , preferably 0.2 mg / cm 2 .

[0016] The present invention also provides a method for preparing a catalytic layer having a layered ionomer distribution, comprising the following steps:

[0017] An ionomer solution and a catalyst slurry are prepared separately; two independently controllable ultrasonic nozzles are provided, and the two ultrasonic nozzles are alternately used to spray an ionomer solution layer and a catalyst slurry layer on a heated substrate, and finally the catalytic layer is obtained.

[0018] Furthermore, the long side chain ionomer in the ionomer solution is diluted with an alcohol solution, and the concentration of the long side chain ionomer after dilution is 0.2-0.3 wt %, preferably 0.25 wt %.

[0019] Furthermore, the Pt / C catalyst in the catalyst slurry is diluted with an alcohol solution, and the concentration of the Pt / C catalyst after dilution is 6-8wt%.

[0020] Furthermore, the alcohol solution is an isopropanol aqueous solution.

[0021] Furthermore, the catalyst slurry is ball-milled for 6-10 hours, preferably 8 hours before spraying.

[0022] Furthermore, the substrate is a woven high-temperature cloth with a PTFE coating.

[0023] Furthermore, the temperature of the substrate during spraying is 80-90°C.

[0024] Furthermore, the spraying injection speed of the catalyst slurry is 0.3-0.5 mL / min, preferably 0.4 mL / min.

[0025] Furthermore, the spraying injection speed of the ionomer solution is 0.18-0.23 mL / min.

[0026] Furthermore, the power of the two ultrasonic nozzles is 8-12W, preferably 10W.

[0027] Furthermore, after each layer is sprayed, wait for at least 10 seconds until it is completely dry.

[0028] The present invention also provides an application of a catalyst layer with layered ionomer distribution in a proton exchange membrane fuel cell, wherein the catalyst layer significantly improves the oxygen mass transfer efficiency and electrochemical performance of the fuel cell.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The present invention realizes the layered spraying of catalyst slurry and ionomer solution through the double-nozzle alternating ultrasonic spraying method, improves the ionomer distribution on the catalyst surface, reduces the local oxygen mass transfer resistance, and constructs an efficient proton conduction network.

[0031] (2) The present invention uses a small amount of short side chain ionomer in the catalyst slurry and separately sprays the long side chain ionomer solution, thereby ensuring the stability of the catalyst slurry and building an efficient proton conduction network, thereby maximizing the utilization efficiency of the Pt / C catalyst.

[0032] (3) The present invention can accurately control the overall ionomer content in the catalyst layer by adjusting the ionomer content in the catalyst slurry and the spraying parameters of the ionomer solution, thereby minimizing the oxygen mass transfer resistance while ensuring the proton conductivity, thereby significantly improving the overall performance of the fuel cell.

[0033] (4) The present invention not only optimizes the distribution of ionomers on the catalyst surface through the synergistic effect of short side chain and long side chain ionomers, but also provides a more complete proton conduction network, ensuring that the fuel cell can maintain high electrochemical performance under different operating conditions.

[0034] (5) The present invention enhances the mechanical strength and structural stability of the catalyst layer through the ingenious design of alternating spraying and multi-layer composite structure. At the same time, the first and last layers are sprayed with ionomer solution to ensure good interface contact with the membrane and gas diffusion layer.

[0035] (6) The present invention adopts dual-nozzle ultrasonic spraying technology, and the preparation process is simple and controllable, without complicated post-processing. Compared with the traditional mixed spraying method, this method is more flexible in process, has higher precision, is easy to achieve large-scale production, and has significant industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a schematic structural diagram of the dual-nozzle ultrasonic spraying system of the present invention.

[0037] Figure 2 It is a schematic diagram of the catalyst layer prepared by the double-nozzle alternating ultrasonic spraying method of the present invention.

[0038] Figure 3 The cell polarization curves of the fuel cell catalyst layers prepared in Example 1 and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0039] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0040] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0041] Specifically, the main raw material information used in the following examples is as follows: the Pt / C catalyst of the high specific surface area carbon carrier adopts TEC10E50E of Tanaka Precious Metals of Japan; the long side chain ionomer adopts Nafion D520 of DuPont of the United States, and the short side chain ionomer adopts Aquivion D79-25BS. The side chain of Nafion is a longer perfluorovinyl ether group with a sulfonic acid group (-SO3H) connected to the end, while the side chain of Aquivion is shorter; the high temperature woven fabric material adopts 25μm model of China Weihang New Materials.

[0042] Embodiment 1:

[0043] This embodiment provides a catalyst layer with a layered ionomer distribution, and the preparation method thereof is as follows:

[0044] S1: Weigh 0.3 g of Pt / C catalyst (Pt mass fraction of 46.7%) and mix with 5.96 g of ultrapure water, 35.74 g of isopropanol and 0.12 g of Aquivion solution (mass fraction of 20%). After ball milling for 8 hours, ultrasonic treatment was performed for 30 minutes to ensure uniform dispersion to obtain a catalyst slurry (I / C = 0.15).

[0045] S2: The Nafion solution (mass fraction of 20%) was diluted to 0.25 wt % with isopropanol, and ultrasonically treated for 30 minutes to ensure uniform dispersion, and then allowed to stand for 24 hours to allow the ionomer solution system to recover stability, thereby obtaining an ionomer solution.

[0046] S3: Use nozzle 1 to spray the catalyst slurry, set the injection speed to 0.4 mL / min; use nozzle 2 to spray the ionomer solution, set the injection speed to 0.2 mL / min, and set the ultrasonic spray power to 10 W.

[0047] S4: Place the PTFE-coated braided high-temperature cloth on the heating platform, adjust the temperature to 85°C, and turn on the vacuum adsorption device to fix the high-temperature cloth on the heating platform.

[0048] S5: Use nozzle 2 to spray a layer of ionomer solution on the surface of the high temperature cloth, and wait for 10 seconds to allow it to dry completely.

[0049] S6: Use the catalyst slurry with I / C of 0.15, alternately use nozzle 1 and nozzle 2 to spray the catalyst slurry and ionomer solution layer by layer, and wait for 10 seconds after each layer is sprayed to make it completely dry. For the catalyst Pt loading of 0.2mg / cm 2 For the catalytic layer, 10 layers of catalyst and 11 layers of ionomer need to be sprayed so that the total I / C of the catalytic layer is maintained at 0.8, and the last layer sprayed is guaranteed to be the ionomer layer.

[0050] Embodiment 2:

[0051] This embodiment provides a catalyst layer with a layered ionomer distribution, and the preparation method thereof is as follows:

[0052] S1: Weigh 0.3 g of Pt / C catalyst (Pt mass fraction of 46.7%) and mix with 5.96 g of ultrapure water, 35.74 g of isopropanol and 0.16 g of Aquivion solution (mass fraction of 20%). After ball milling for 8 hours, ultrasonic treatment was performed for 30 minutes to ensure uniform dispersion to obtain a catalyst slurry (I / C = 0.20).

[0053] S2: The Nafion solution (mass fraction of 20%) was diluted to 0.25 wt % with isopropanol, and ultrasonically treated for 30 minutes to ensure uniform dispersion, and then allowed to stand for 24 hours to allow the ionomer solution system to recover stability, thereby obtaining an ionomer solution.

[0054] S3: Use nozzle 1 to spray the catalyst slurry, set the injection speed to 0.4 mL / min; use nozzle 2 to spray the ionomer solution, set the injection speed to 0.18 mL / min, and set the ultrasonic spray power to 10 W.

[0055] S4: Place the PTFE-coated braided high-temperature cloth on the heating platform, adjust the temperature to 85°C, and turn on the vacuum adsorption device to fix the high-temperature cloth on the heating platform.

[0056] S5: Use nozzle 2 to spray a layer of ionomer solution on the surface of the high temperature cloth, and wait for 10 seconds to allow it to dry completely.

[0057] S6: Use the catalyst slurry with I / C of 0.15, alternately use nozzle 1 and nozzle 2 to spray the catalyst slurry and ionomer solution layer by layer, and wait for 10 seconds after each layer is sprayed to make it completely dry. For the catalyst Pt loading of 0.2mg / cm 2 For the catalytic layer, 10 layers of catalyst and 11 layers of ionomer need to be sprayed so that the total I / C of the catalytic layer is maintained at 0.8, and the last layer sprayed is guaranteed to be the ionomer layer.

[0058] Embodiment 3:

[0059] This embodiment provides a catalyst layer with a layered ionomer distribution, and the preparation method thereof is as follows:

[0060] S1: Weigh 0.3 g of Pt / C catalyst (Pt mass fraction of 46.7%) and mix with 5.96 g of ultrapure water, 35.74 g of isopropanol and 0.04 g of Aquivion solution (mass fraction of 20%). After ball milling for 8 hours, ultrasonic treatment was performed for 30 minutes to ensure uniform dispersion to obtain a catalyst slurry (I / C = 0.05).

[0061] S2: The Nafion solution (mass fraction of 20%) was diluted to 0.25 wt % with isopropanol, and ultrasonically treated for 30 minutes to ensure uniform dispersion, and then allowed to stand for 24 hours to allow the ionomer solution system to recover stability, thereby obtaining an ionomer solution.

[0062] S3: Use nozzle 1 to spray the catalyst slurry, set the injection speed to 0.4 mL / min; use nozzle 2 to spray the ionomer solution, set the injection speed to 0.23 mL / min, and set the ultrasonic spray power to 10 W.

[0063] S4: Place the PTFE-coated braided high-temperature cloth on the heating platform, adjust the temperature to 85°C, and turn on the vacuum adsorption device to fix the high-temperature cloth on the heating platform.

[0064] S5: Use nozzle 2 to spray a layer of ionomer solution on the surface of the high temperature cloth, and wait for 10 seconds to allow it to dry completely.

[0065] S6: Use the catalyst slurry with I / C of 0.15, alternately use nozzle 1 and nozzle 2 to spray the catalyst slurry and ionomer solution layer by layer, and wait for 10 seconds after each layer is sprayed to allow it to dry completely. For the catalyst Pt loading of 0.2 mg / cm 2 For the catalytic layer, 10 layers of catalyst and 11 layers of ionomer need to be sprayed so that the total I / C of the catalytic layer is maintained at 0.8, and the last layer sprayed is guaranteed to be the ionomer layer.

[0066] Comparative Example 1:

[0067] This comparative example is a catalyst layer prepared by a conventional spraying method, and the specific preparation method is as follows:

[0068] S1: Weigh 0.3 g of Pt / C catalyst (Pt mass fraction of 46.7%) and mix with 5.96 g of ultrapure water, 35.74 g of isopropanol and 0.64 g of Nafion solution (mass fraction of 20%). After ball milling for 8 hours, ultrasonic treatment was performed for 30 minutes to ensure uniform dispersion to obtain a catalyst slurry (I / C = 0.80).

[0069] S2: Use the nozzle to spray the catalyst slurry, set the injection speed to 0.4 mL / min, and the ultrasonic spray power to 10 W.

[0070] S3: Place the PTFE-coated braided high-temperature cloth on the heating platform, adjust the temperature to 85°C, and turn on the vacuum adsorption device to fix the high-temperature cloth on the heating platform.

[0071] S4: Repeat the spraying process for 10 layers according to the path until the catalytic layer loading reaches 0.20 mg / cm 2 .

[0072] The catalytic layers prepared in Example 1 and Comparative Example 1 were assembled into single cells for electrochemical testing. The electrochemical testing was performed using a fuel cell testing station (Scribner Associates Inc., 850e) at 80°C, 100% relative humidity, and H2 / Air.

[0073] The assembly process of the fuel cell includes: first, the MEA is fixed to the two sides of the proton exchange membrane (Nafion 212) by hot pressing, with a pressure of 0.45MPa and a temperature of 145°C. The prepared membrane electrode assembly (MEA) is clamped between two carbon paper gas diffusion layers (GDL) with microporous layers, and then assembled into a single cell. During the assembly process, the active electrode area of ​​the MEA is set to 2cm×2cm, and it needs to be activated at fixed voltages of 0.8V, 0.6V and 0.4V before use.

[0074] The test conditions of the polarization curve are as follows: the cathode and anode are supplied with air with 100% relative humidity and high-purity hydrogen, respectively, with flow rates of 0.4L / min and 0.2L / min, respectively. The battery temperature is maintained at 80°C and the operating pressure is 150kPa absolute pressure.

[0075] Depend on Figure 3 The results show that the membrane electrode prepared by the dual-nozzle alternating spraying method of the present invention has a significant performance improvement compared with the traditional mixed spraying method. In the high current density region, the polarization of the fuel cell is significantly reduced, indicating that the oxygen mass transfer process has been improved. This significant performance improvement is mainly attributed to the dual-nozzle alternating ultrasonic spraying method adopted by the present invention. By spraying the catalyst slurry and the ionomer solution separately, the formation of an excessively thick ionomer coating layer on the catalyst surface is avoided, and the local oxygen mass transfer resistance is significantly reduced; at the same time, an efficient proton conduction network is constructed through the synergistic effect of short side chain and long side chain ionomers, thereby improving the catalyst utilization. The composite catalytic layer structure formed by alternating spraying helps to reduce the amount of ionomer adsorption on the catalyst surface and reduce the thickness of the ionomer thin layer, thereby reducing the local oxygen mass transfer resistance. At the same time, it optimizes the distribution of the catalyst and the ionomer, improves the formation efficiency of the three-phase interface, reduces the overall mass transfer resistance, thereby improving the utilization of the catalyst, and ultimately enhancing the efficiency of the electrochemical reaction.

[0076] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A catalyst layer having a layered ionomer distribution, characterized in that: The catalytic layer is a multi-layer composite structure, which includes an ionomer solution layer and a catalyst slurry layer which are alternately sprayed on the substrate layer by layer; The ionomer in the ionomer solution layer is a long side chain ionomer; The slurry of the catalyst slurry layer includes short side chain ionomer and Pt / C catalyst, wherein the mass ratio of the short side chain ionomer to the carbon carrier is 0.05-0.

2.

2. A catalyst layer with stratified ionomer distribution according to claim 1, characterized in that: The catalyst layer has N layers in total, where N is an odd number; wherein the 1st, 3rd, 5th ... Nth layers are ionomer solution layers, and the 2nd, 4th, 6th ... (N-1)th layers are catalyst slurry layers.

3. The catalyst layer with stratified ionomer distribution according to claim 1, characterized in that: The long side chain ionomer is selected from Nafion series ionomers, and the short side chain ionomer is selected from Aquivion series ionomers.

4. The catalyst layer with stratified ionomer distribution according to claim 1, characterized in that: The total mass ratio of the ionomer to the carbon carrier in the catalyst layer is 0.75-0.85, and the platinum loading is 0.15-0.25 mg / cm 2 .

5. A method for preparing a catalytic layer having a layered ionomer distribution according to any one of claims 1 to 4, characterized in that: The following steps are involved: An ionomer solution and a catalyst slurry are prepared separately; two independently controllable ultrasonic nozzles are provided, and the two ultrasonic nozzles are alternately used to spray an ionomer solution layer and a catalyst slurry layer on a heated substrate, and finally the catalytic layer is obtained.

6. The method for preparing a catalyst layer having a layered ionomer distribution according to claim 5, characterized in that: The long side chain ionomer in the ionomer solution is diluted with an alcohol solution, and the concentration of the long side chain ionomer after dilution is 0.2-0.3wt%; The Pt / C catalyst in the catalyst slurry is diluted with an alcohol solution, and the concentration of the diluted Pt / C catalyst is 6-8wt%; the catalyst slurry is ball-milled for 6-10 hours before spraying.

7. The method for preparing a catalyst layer having a layered ionomer distribution according to claim 5, characterized in that: The substrate is a woven high-temperature cloth with a PTFE coating, and the temperature of the substrate during spraying is 80-90°C.

8. The method for preparing a catalyst layer having a layered ionomer distribution according to claim 5, characterized in that: The spraying injection speed of the catalyst slurry is 0.3-0.5 mL / min, the spraying injection speed of the ionomer solution is 0.18-0.23 mL / min, and the power of the two ultrasonic nozzles is 8-12W.

9. The method for preparing a catalyst layer having a layered ionomer distribution according to claim 5, characterized in that: Wait at least 10 seconds after each spraying to allow it to dry completely.

10. Use of the catalyst layer with stratified ionomer distribution according to any one of claims 1 to 4 in a proton exchange membrane fuel cell.

Citation Information

Patent Citations

  • Proton exchange composite membrane and continuous preparation method thereof

    CN114204089A

  • Preparation method for improving proton conduction of catalyst layer of fuel cell

    CN114899419A

  • Preparation method of cathode catalyst layer, preparation method of membrane electrode and membrane electrode

    CN116487614A

  • Hydrogen-oxygen fuel cell catalyst layer with multi-component ionomer gradient distribution structure and preparation method of hydrogen-oxygen fuel cell catalyst layer

    CN116979069A

  • Catalyst layer for fuel cell, electrolyte membrane-electrode assembly, and fuel cell

    JP2019140010A